The Application of Hyaluronic Acid-Based Hydrogels in Bone and Cartilage Tissue Engineering - Hongru Li; Zhiping Qi; Shuang Zheng; Yuxin Chang; Weijian Kong; Chuan Fu; Ziyuan Yu; Xiaoyu Yang; Su Pan (Advances in Materials Science and Engineering)
At present, the healing of osteopathy, especially the healing of cartilage, has been proven to be difficult. Commonly used treatment methods are autogenous bone grafts and allogeneic bone grafts, but grafts cannot fully meet the clinical treatment requirements due to problems related to the source, price, immunity, and other concerns. Thus, the combination of biomaterials and tissue engineering technology has become a new direction in research. Among studies on tissue engineering bone and cartilage materials, hydrogels that show biological activity, absorbability after degradability, plasticity, and easy preparation have become the focus. Hydrogels are used as extracellular matrix mimics. Although various materials are able to form hydrogels, hyaluronic acid and its derivatives are prominently used. Hyaluronic acid hydrogels have many advantages, such as promoting cell adhesion and proliferation and wound healing. They also demonstrate sufficient biological activity for stimulating a microenvironment for cell survival. However, their disadvantages require further modification and include a poor degradation rate and insufficient mechanical performance. In this paper, hyaluronic acid-based hydrogels, their modifications, applications, and mechanisms, as well as new techniques for processing hyaluronic acid hydrogels in bone and cartilage tissue engineering, are briefly reviewed, and their future prospects and directions for future work are discussed.